Physical activity and academic achievement: an analysis of potential student- and school-level moderators - Hannah K. Behringer; Emilie R. Saksvig; Peter J. Boedeker; Paul N. Elish; Christi M. Kay; Hannah G. Calvert; Adria M. Meyer; Julie A. Gazmararian (BMC, 2022)
Abstract Background Many children do not engage in sufficient physical activity, and schools provide a unique venue for children to reach their recommended 60 daily minutes of moderate-to-vigorous physical activity (MVPA). Prior research examining effects of MVPA on academic achievement is inconclusive, and few studies have investigated potential moderators of this relationship. This study examined whether student-level characteristics (gender, race/ethnicity, free/reduced-price lunch status) and school-level characteristics (proportion of students qualifying for free/reduced-price lunch, physical activity environment and opportunities) moderate the relationship between MVPA and academic achievement. Methods In a large, diverse metropolitan public school district in Georgia, 4,936 students in Grade 4 were recruited from 40 elementary schools. Students wore accelerometers to measure school-day MVPA for a total of 15 days across three semesters (fall 2018, spring 2019, fall 2019). Academic achievement data, including course marks (grades) for math, reading, spelling, and standardized test scores in writing, math, reading, and Lexile (reading assessment), were collected at baseline (Grade 3, ages 8-9) and at follow-up in Grade 4 (ages 9-10). Standardized test scores were not measured in Grade 5 (ages 10-11) due to COVID-19-related disruptions. Multilevel modeling assessed whether student-level and/or school-level characteristics were moderators in the cross-sectional and longitudinal MVPA-academic achievement relationship. Results Cross sectional analyses indicated that the MVPA and AA relationship was moderated only by student Hispanic ethnicity for Grade 4 fall spelling marks (β = -0.159 p < 0.001). The relationship for Grade 4 fall spelling marks was also moderated by school physical activity opportunities (β = -0.128 (p < 0.001). Longitudinally, there was no significant moderation of the MVPA-academic achievement. A relationship by student gender, free/reduced-price lunch status, race/ethnicity; nor for school-level factors including proportion of students qualifying for free/reduced-price lunch, physical activity environment, and physical activity opportunities. Conclusions Overall, our results did not suggest that student- or school-level characteristics moderate the MVPA-academic achievement relationship. While statistically significant results were observed for certain outcomes, practical differences were negligible. In this population, school-based MVPA does not appear to differently affect academic performance based on student gender, race/ethnicity, free/reduced-price lunch, nor school characteristics. Trial registration This study was registered with the National Institutes of Health (NIH) ClinicalTrials.gov system, with ID NCT03765047 . Registered 05 December 2018-Retrospectively registered.